Coffea arabica L. Resistant to Coffee Berry Borer (Hypothenemus hampei) Mediated by Expression of the Bacillus thuringiensis Cry10Aa Protein - Valencia-Lozano, Eliana; Cabrera-Ponce, Jose Luis; Noa-Carrazana, Juan C.; Ibarra, Jorge E. (Frontiers in Plant Science, 2021)
Coffea spp. are tropical plants used for brewing beverages from roasted and grounded seeds, the favorite drink in the world. It is the most important commercial crop plant and the second most valuable international commodity after oil. Global coffee trade relies on two Coffea species: C. arabica L. (arabica coffee) comprising 60% and C. canephora (robusta) comprising the remaining 40%. Arabica coffee has lower productivity and better market price than robusta. Arabica coffee is threatened by disease (i.e., coffee leaf rust), pests [i.e., Hypothenemus hampei or coffee berry borer (CBB) and nematodes], and susceptibility to climate change (i.e., drought and aluminum toxicity). Plant biotechnology by means of tissue culture inducing somatic embryogenesis (SE) process, genetic transformation, and genome editing are tools that can help to solve, at least partially, these problems. This work is the continuation of a protocol developed for stable genetic transformation and successful plant regeneration of arabica coffee trees expressing the Bacillus thuringiensis (Bt) toxin Cry10Aa to induce CBB resistance. A highly SE line with a high rate of cell division and conversion to plants with 8-month plant regeneration period was produced. To validate this capability, gene expression analysis of master regulators of SE, such as BABY BOOM (BBM), FUS3, and LEC1, embryo development, such as EMB2757, and cell cycle progression, such as ETG1 and MCM4, were analyzed during induction and propagation of non-competent and highly competent embryogenic lines. The particle bombardment technique was used to generate stable transgenic lines after 3 months under selection using hygromycin as selectable marker, and 1 month in plant regeneration. Transgenic trees developed fruits after 2 years and demonstrated expression of the Bt toxin ranging from 3.25 to 13.88 μg/g fresh tissue. Bioassays with transgenic fruits on CBB first instar larvae and adults induced mortalities between 85 and 100% after 10 days. In addition, transgenic fruits showed a seed damage lower than 9% compared to 100% of control fruits and adult mortality. This is the first report on stable transformation and expression of the Cry10Aa protein in coffee plants with the potential to control CBB.